Factors influencing prolonged length of hospital stay and ICU admission in a pediatric population admitted with infectious SARS - Dandiany C. SOFKA; Marinei C. RICIERI; Mariana M. FACHI; Lucas M. OKUMURA; Victor H. COSTA JUNIOR; Fábio A. MOTTA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: During the COVID-19 pandemic the largest exclusively pediatric hospital in Brazil created a care pathway (CPW) for patients admitted with infectious severe acute respiratory syndrome (SARS). We aimed at identifying factors associated with prolonged hospital length of stay (LOS) and intensive care unit (ICU) admission of children with infectious SARS. Methods: Retrospective cohort study that included pediatric patients with infectious SARS through March to September 2020, when COVID-19 dissemination arose locally. The primary study outcomes were hospital length of stay and ICU admission, which were considered as dependent variables in univariate analysis, followed by logistic regression multivariate model. Variables with p-values <0.05 were considered statistically significant. Results: 122 hospitalized patients were identified. The factors associated with prolonged hospitalization and ICU admission were female (β 0.753, p=0.000), public health care (β 0.903, p=0.000), respiratory comorbidity (β 0.610, p=0.000), with comorbidity (β 0.610, p=0.000) and COVID-19 (β 1.796, p=0.000). Moreover, with comorbidity (OR 3.182, p=0.017), X-ray alterations (OR 6.126, p=0.003) and COVID-19 (OR 6.284, p=0.005) were the independent factor and predictor of ICU admission at SARS-CPW. Conclusions: Children with SARS with certain comorbidities and other respiratory diseases were considered to be at risk because they were associated with prolonged length of stay and greater ICU admission. The results suggest that interventions focused on these groups may be essential to optimize the management of CPW-SARS, avoids dissemination of infectious disease and promotes better results and resource allocation.